2014
DOI: 10.1016/j.carbon.2014.06.077
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement in melt-processed polymer–graphene composites at extremely low graphene loading level

Abstract: We have prepared polymer nanocomposites reinforced with exfoliated graphene layers solely via melt blending. For this study polyethylene terephthalate (PET) was chosen as the polymer matrix due to its myriad of current and potential applications. PET and PET/graphene nanocomposites were melt compounded on an internal mixer and the resulting materials were compression molded into films. Transmission electron microscopy and scanning electron microscopy revealed that the graphene flakes were randomly orientated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 51 publications
2
96
1
3
Order By: Relevance
“…The aspect ratio of the f-GNPs used here was found to be 432, which is comparable to material used in previous studies, which ranged from 90 to 933. 9,[59][60][61] However it has been suggested that aspect ratios as high as 35 000 are needed for full stress transfer into the filler particles, [62][63][64] implying that the current system will not achieve optimized reinforcement. It was also noted that the presence of functional groups on the f-GNPs may improve the interfacial stress transfer.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…The aspect ratio of the f-GNPs used here was found to be 432, which is comparable to material used in previous studies, which ranged from 90 to 933. 9,[59][60][61] However it has been suggested that aspect ratios as high as 35 000 are needed for full stress transfer into the filler particles, [62][63][64] implying that the current system will not achieve optimized reinforcement. It was also noted that the presence of functional groups on the f-GNPs may improve the interfacial stress transfer.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…The process does not necessitate the usage of expensive solvents such as the ones currently being used in literature for exfoliation of graphite (THF and NMP) [27,24], and it is compatible with large-scale industrial processes. Table 2 also indicates a higher electrical conductivity proving that the graphene doped thermoplastic polyurethane is moderately conductive.…”
Section: Cyclic Compression Testsmentioning
confidence: 99%
“…In this regard, their properties can be tailored through the inclusion of nanofillers to their structure [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly problematic for high aspect ratio 2D fillers which can show aggregation effects even at loading levels below 0.5%. 45,46,50,51 Such aggregation is almost always detrimental to the properties of the composite, for example resulting in fall off in mechanical properties. 46 Alternatively for optical applications, well defined properties associated with monolayers might be required which would be destroyed by aggregation.…”
Section: Introductionmentioning
confidence: 99%